A new species of Cryptalyra (Hymenoptera, Megalyridae) from Brazil with a key to species of the genus - Azevedo, C. O.; Tavares, M. T. (Zootaxa, 2006)
Cryptalyra depressa sp. nov. is described and illustrated based on a specimen from state of Pará, Brazil. This species is easily recognizable by having a wide longitudinal depression along the propodeum. A key to species based on females is presented.